A Collaborative Auto-ethnographic Study of Indonesian Higher Degree Research Students’ Adaptation in Anglophone Universities - Effendi Limbong; Nizamuddin Sadiq; Ridha Mardiani (Script Journal: Journal of Linguistics and English Teaching, 2025)
Background: This research explores the experiences of Indonesian doctoral students in English-speaking universities through a collaborative auto-ethnographic approach. Utilising Schartner and Young's (2016) stress and coping strategies and culture-learning frameworks, we analyse narrative data to investigate our academic and sociocultural journeys in the US, UK, and Australia.   Methodology: To attain a profound comprehension, we participate in personal and group introspection, analysis, and interpretation, utilising imaginative thought, creativity, emotional self-exploration, and ongoing dialogues. The study identifies four major psychological adaptation themes (social support, survival, spirituality, and compliance), a critical socio-cultural adaptation theme (feeling like cultural aliens), and a vital academic adaptation theme (questioning our academic capability amid struggles with critical reading and writing).   Findings: The findings reveal three themes: Psychological Aspects: “Social Support, Survival, Spirituality, and Compliance”, Sociocultural Aspect: “We Are Cultural Aliens”, Academic Aspect: “Questioning Our Academic Capacity as We Struggled to Read and Write Critically”.   Conclusion: The findings underscore the significance of awareness and emphasise the necessity for effective adaptation among international doctoral students. This research contributes valuable insights into the challenges faced by Indonesian doctoral students in Anglophone academic settings, shedding light on the importance of support systems, cultural understanding, and academic confidence stop where for a successful academic journey.   Originality: While previous studies have largely examined the difficulties faced during adaptation, the way these challenges ultimately lead to successful outcomes remains under-explored. This research seeks to address this deficiency by investigating how Indonesian international research students in Anglophone universities convert cultural, psychological, and academic obstacles into successful adaptation.